2012
DOI: 10.2165/11598940-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness and Cost-Utility of Beclomethasone/Formoterol versus Fluticasone Propionate/Salmeterol in Patients with Moderate to Severe Asthma

Abstract: Overall, from the Italian NHS perspective, BDP/F treatment is associated with a reduction in cost and offers a slight increase of effectiveness in terms of weeks spent in successful control and QALYs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…These improvements are associated with better health-related quality of life [122, 130, 131] and cost-effectiveness [132, 133]. Additionally, in most studies the Authors observed that the mean daily dose of iCSs was much higher for the large particle aerosols compared to the small particle aerosols of BDP/Form.…”
Section: Introductionmentioning
confidence: 99%
“…These improvements are associated with better health-related quality of life [122, 130, 131] and cost-effectiveness [132, 133]. Additionally, in most studies the Authors observed that the mean daily dose of iCSs was much higher for the large particle aerosols compared to the small particle aerosols of BDP/Form.…”
Section: Introductionmentioning
confidence: 99%
“…5 of 20 patients in the irst group versus 12 of 20 patients in the second with a statistically signi icant difference (p 0.02). In a work of 2013, Kew and other [20] evaluated the ef icacy and safety of budesonide/formoterol in a single inhaler used for maintenance and rescue therapy compared with the use of luticasone/salmeterol or budesonide/formoterol in combination with salbutamol as rescue medication. The results obtained showed that patients treated with the combination budesonide/formoterol, both as maintenance therapy that as emergency therapy, showed a lower number of asthma exacerbations, fewer hospitalizations and a reduction in the use of oral steroids compared patients treated with SABA as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies (16%) did not report any funding sources. Most of the CEA studies using effectiveness evidence (7/8, 87.5%) (7,15,16,22,25,31) reported that the interventions were cost-effective, while only 4 out of 9 (44.4%) (18,20,28,32) CEA studies using efficacy evidence were cost-effective.…”
Section: Discussionmentioning
confidence: 99%